2007
DOI: 10.1016/j.exer.2007.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Injury and nucleotides induce phosphorylation of epidermal growth factor receptor: MMP and HB-EGF dependent pathway

Abstract: The early events that occur rapidly after injury trigger signal cascades that are essential for proper wound closure of corneal epithelial cells. We hypothesize that injury releases ATP, which stimulates purinergic receptors and elicits the phosphorylation of epidermal growth factor receptor (EGFR) tyrosine residues and subsequent cell migration by a MMP and HB-EGF dependent pathway. We demonstrated that the inhibition of purinergic receptors with the antagonist, Reactive Blue 2, abrogated the phosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 43 publications
4
77
0
Order By: Relevance
“…Purse strings can nonetheless form at the leading edges of moving epithelial cell sheets because EGFR activation occurs only at straight and convex edges. Wounding sheets of corneal epithelial cells causes release of heparin-binding EGF-like growth factor and amphiregulin (19,20,22,32). Both of these ligands bind strongly to negatively charged glycans in the extracellular matrix and the cell surface (56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Purse strings can nonetheless form at the leading edges of moving epithelial cell sheets because EGFR activation occurs only at straight and convex edges. Wounding sheets of corneal epithelial cells causes release of heparin-binding EGF-like growth factor and amphiregulin (19,20,22,32). Both of these ligands bind strongly to negatively charged glycans in the extracellular matrix and the cell surface (56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…The EGFR is activated upon wounding epithelial cell sheets (17)(18)(19)(20)(21)(22)(23). The finding that EGFR signaling disrupts purse strings suggested that activation occurs only at straight and convex edges.…”
Section: Egfr Signaling Is Selectively Activated At Convex and Straigmentioning
confidence: 99%
See 2 more Smart Citations
“…During skin wound healing, the release of extracellular ATP has been shown to be critical for efficient epithelial repair, revealing the role of purinergic signaling in general cell functions. Indeed, activation of ATP receptors stimulates the proliferation of epidermal keratinocytes (Greig et al, 2003) and smooth muscle cells (Wilden et al, 1998), and initiates migration of epithelial cells (Boucher et al, 2007). Likewise, extracellular ATP released from hepatocytes and Kupffer cells immediately after hepatectomy has been shown to promote liver regeneration (Gonzales et al, 2010).…”
Section: Purinergic Signaling In Cancermentioning
confidence: 99%